Information independence and common knowledge - Olivier Gossner; Ehud Kalai; Robert Weber (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
Conditions of information independence are important in information economics and game theory. We present notions of partial independence in Bayesian environments, and study their relationships to notions of common knowledge.
Keywords: 330; Bayesian games; independent types; common knowledge